A New Genus for a New Oribatid Mite Species (Oribatei, Ceratozetoidea) from the Ukraine - Pavlitshenko, P.G. (Вестник зоологии, 1993)
Type material of the new species, assigned here to a new genus is deposited in the Schmalhausen Institute of Zoology, Kiev. Ceresella (Lat.) — deminutive, endearment term from Ceres. Roman goddess of fields, agriculture, rural lifer and cereals, daughter of Saturnus and Rhea, mother of Proserpina.